2016
DOI: 10.3109/02652048.2016.1142016
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised alginate flow seeding microparticles for use in Particle Image Velocimetry (PIV)

Abstract: Alginate microparticles as flow seeding fulfil all the requirements that are recommended for the velocity measurements in Particle Image Velocimetry (PIV). These spherical microparticles offer the advantage of being environmentally friendly, having excellent seeding properties and they can be produced via a very simple process. In the present study, the performances of alginate microparticles functionalised with a fluorescent dye, Rhodamine B (RhB), for PIV have been studied. The efficacy of fluorescence is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Within the 7% and 42% samples no individual RBC was visible, due to the opaqueness of blood. It has already been shown, that the alginate microspheres are well suited as tracer particles in PIV and PLIF at low particle fractions and even fluorescein or other dyes can be added to further improve the traceability (Kertzscher et al 2008;Ertürk et al 2013;Varela et al 2016). By using deformable microspheres, the results would be more comparable to the actual cell movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the 7% and 42% samples no individual RBC was visible, due to the opaqueness of blood. It has already been shown, that the alginate microspheres are well suited as tracer particles in PIV and PLIF at low particle fractions and even fluorescein or other dyes can be added to further improve the traceability (Kertzscher et al 2008;Ertürk et al 2013;Varela et al 2016). By using deformable microspheres, the results would be more comparable to the actual cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…They have already been used with larger diameter as sufficient tracer particles with a small particle fraction to investigate near wall flows (wall Particle Image Velocimetry (PIV)) (Kertzscher et al 2008). Ertürk et al (2013) used approximately 20 μm alginate microspheres with fluorescein as tracer particles in oil and air flow and Varela et al (2016) functionalized them with Rhodamin B and showed the applicability in PIV and Planar Laser-Induced Fluorescence (PLIF). The microspheres are suitable to follow the flow in a liquid as their porous structure allows them to take on the density of the surrounding fluid (Ertürk et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was possible to detect the movements of individual microspheres at a particle fraction of 5 % in the center of the microchannel. It has already been shown, that the alginate microspheres are well suited as tracer particles in PIV and PLIF at low particle fractions and even fluorescein or other dyes can be added to further improve the traceability (Kertzscher et al, 2008;Ertürk et al, 2013;Varela et al, 2016). By using deformable microspheres, the results would be more comparable to the actual cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…They have already been used with larger diameter as sufficient tracer particles with a small particle fraction to investigate near wall flows (wall Particle Image Velocimetry (PIV)) (Kertzscher et al, 2008). Ertürk et al (2013) used approximately 20 µm alginate microspheres with fluorescein as tracer particles in oil and air flow and Varela et al (2016) functionalized them with Rhodamin B and showed the applicability in PIV and Planar Laser-Induced Fluorescence (PLIF). The microspheres are suitable to follow the flow in a liquid as their porous structure allows them to take on the density of the surrounding fluid (Ertürk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further details are provided by Ertürk et al [16], where it is demonstrated that alginate particles are very suitable for PIV application in turbo-machinery, on the mineral oil is the principal working fluid. More recently, Varela et al [25] explained in more details other PIV applications where the capability of controlling the diameter and their porosity provide great advantages in front of other seeders like air-bubbles [15]. Gaussian geometric optics limit the smallest size of the distinguishable particle.…”
Section: Particle Piv and Working Fluid Requirementsmentioning
confidence: 99%